2022
DOI: 10.1177/20414196221104146
|View full text |Cite
|
Sign up to set email alerts
|

Review on quick safety assessment of building structures in complex urban environment after extreme explosion events

Abstract: Extreme explosion events result in demands for emergency rescue service. From the civil engineering perspective, a quick safety assessment of building structures in the explosion’s vicinity will provide the emergency rescue committee with concrete support to make scientific decisions. In this paper, three primary issues, namely, inverse analysis of explosive characteristics, blast wave propagation in complex urban areas and blast-induced damage identification, are reviewed. These are often performed stepwise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…It reveals that a mesh size larger than 25 mm produces slightly unstable values for stresses, creating inaccurate blast loading results. This is relatively similar to other studies in the area [45][46][47]. However, a mesh element size smaller than 15 mm is an unnecessary value as stress has reached a stable value where convergence time significantly increases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It reveals that a mesh size larger than 25 mm produces slightly unstable values for stresses, creating inaccurate blast loading results. This is relatively similar to other studies in the area [45][46][47]. However, a mesh element size smaller than 15 mm is an unnecessary value as stress has reached a stable value where convergence time significantly increases.…”
Section: Discussionsupporting
confidence: 89%
“…Segments are unaware of venting holes for pressure, calculating results in spite of the pressure load acting on other segments. Whilst this characteristic is expected for empirical blast models and acceptable for calculating blast responses [45][46][47], further development using MM-ALE simulations will provide further insight into blast loading and pressure dissipation on hyperloop structures. This will form a part of our future research.…”
Section: Discussionmentioning
confidence: 99%
“…While a great deal is known about free-field explosions and their propagation across large distances without the presence of obstacles [8][9][10], research efforts are currently focussed on various built environment aspects as these are far less well understood. These include building geometry in singular structure experiments [11][12][13][14], environmental landscapes [15], protective structures [16,17], and the influence of cities [18][19][20] and street configurations [20,21], for example. For a review of blast wave interaction effects with structures conceptualised as obstacles, the reader is directed to Isaac et al [22], while Radcliff et al [23] contain a comprehensive review of blast loading in urban settings.…”
Section: Introductionmentioning
confidence: 99%
“…As laboratory studies are usually conducted at a smaller scale than real-life city explosions (for reasons of space availability, cost, and repeatability), the ability to perform small-scale "urban explosion" test cases to validate city-scale predictive modelling would be extremely attractive. Additionally, Shi et al [19] found that a large body of small-scale explosive trials can provide researchers with a reliable understanding of the structure's effects on blast wave propagation. Furthermore, it is important to determine whether these scaling laws are valid for an isolated building outside the areas of well-known blast-facing scenarios prior to tackling the complexities found in cityscapes.…”
Section: Introductionmentioning
confidence: 99%